2017
DOI: 10.18571/acbm.143
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência De Enteroparasitas Na Região Metropolitana De Fortaleza, Ceará

Abstract: RESUMOAs enteroparasitoses são problemas de saúde pública associadas às condições socioeconômicas, principalmente pela falta de conhecimento de bons hábitos sanitários da população. Nesse ínterim, o presente trabalho objetivou a analisar prevalência de enteroparasitas em amostras fecais provenientes de pacientes da rede pública e privada da Região Metropolitana de Fortaleza -CE. A pesquisa se caracteriza em um estudo transversal, conduzido no período de abril/2014 a novembro/2016, com indivíduos provenientes d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
1
0
0
1
Order By: Relevance
“…A high frequency of infections is observed in children aged 0 to 11 years. Our results corroborate this observation (Almeida-Filho et al 2017;Bezerra et al 2019;Rocha et al 2019;Lima et al 2020). Zaratin et al (2018) also report similar results, and further demonstrate that intestinal parasitosis is more frequent among children in whom personal health and hygiene habits are not well developed.…”
Section: Resultssupporting
confidence: 93%
“…A high frequency of infections is observed in children aged 0 to 11 years. Our results corroborate this observation (Almeida-Filho et al 2017;Bezerra et al 2019;Rocha et al 2019;Lima et al 2020). Zaratin et al (2018) also report similar results, and further demonstrate that intestinal parasitosis is more frequent among children in whom personal health and hygiene habits are not well developed.…”
Section: Resultssupporting
confidence: 93%
“…Dentre as espécies de enteroparasitas que foram encontradas nos exames das amostras das crianças que participaram da pesquisa a maior prevalência foi de Entamoeba coli (35,72%, n=5), Endolimax nana (28,57%, n=4), Entamoeba histolytica (21,43%, n=3), Giardia lamblia (14,28%, n=2). A prevalência dos parasitas encontrados, se assemelham a dados descritos na literatura nacional, de diversas regiões do país, assim como mostram as pesquisas de Magalhães (2013), Almeida Filho (2017 e Silva et al (2018).…”
Section: Resultsunclassified
“…In contrast, higher prevalences were reported in studies conducted in Brazil Northeast region. Filho et al (2017) found a prevalence of 12.73% (840/6,596) of parasites in individuals from the metropolitan region of Fortaleza, Ceará (CE). Accordingly, another study observed that 23.3% (295/1,266) of samples analyzed from individuals using the Sistema Único de Saúde (SUS), in the city of Limoeiro do Norte, CE, were positive for parasites, where E. nana and E. coli were observed in 44.2% and 27.4% of samples respectively (Maia et al, 2015).…”
Section: Discussionmentioning
confidence: 99%